Beobachtungen zur diachronischen Entwicklung der Verbal-periphrase GEHEN + PARTIZIP PERFEKT im italienisch-spanischen Sprachvergleich - Mayr, Paul (Linguistik Online, 2021)
The verbal periphrases constitute a typological feature of the Romance languages and they are especially frequent in the Iberoromanic languages. In the context of this paper the diachronic evolution of the Italian periphrase andare + participio passato, which has a diathetic, modal and resultative function, and its formal, but not functional equivalent in Spanish, ir + participio pasado, will be analysed. The study will focus on the analysis of semantic and functional values of these verbal constructions in different historical phases of the Italian and (European) Spanish language in order to investigate the convergences and divergences which arise between the two languages. In addition, some equivalent constructions in other Romance languages, e. g. Catalan and Portuguese, will occasionally be taken in consideration.